Structure-conductivity relationship of PrBaMnMoO6-δ through in-situ measurements: A neutron diffraction study. Issue 1 (1st January 2021) - Afroze, Shammya; Torino, Nico; Reza, Md Sumon; Radenahmad, Nikdalila; Cheok, Quentin; Henry, Paul F.; Azad, Abul K.
Abstract: The structural and electrochemical properties of the double perovskite-type oxide, PrBaMnMoO6-δ, was investigated using neutron diffraction with in-situ conductivity measurement under a dry Argon atmosphere from 25 °C to 700 °C. A Rietveld refinement of the neutron diffraction data confirmed monoclinic symmetry in the P2 1 /n space group. Rietveld refinement also confirms the unit cell parameters of a = 5.6567 (1) Å, b = 5.6065 (2) Å, c = 7.9344 (1) Å and β = 84.43° with reliable atomic positions and refinement factors (R-factors). Neutron diffraction data refinement shows two minor phases (<5%), an orthorhombic AB2 O5 type phase of PrMn2 O5 in the Pbam (No. 32) space group with unit cell parameters, a = 7.9672 (1) Å, b = 8.9043 (2) Å and c = 5.8540 (1) Å and a scheelite phase of BaMoO4 in the tetragonal I41 /a (88) space group with the unit cell parameters, a = b = 5.9522 (1) Å, and c = 12.3211 (2) Å. Morphological images revealed a porous and intertwined microstructure. In-situ conductivity measurement shows that the total conductivity of this material was 130.84 Scm −1 at 700 °C.